Sustainable wetland management for wildlife and people at Koshi Tappu Wildlife Reserve - Thapa, I; Dahal, BR (Banko Janakari, 2009)
Koshi Tappu Wildlife Reserve (KTWR) which lies in the lowlands of eastern Nepal is the most important wetland for migratory water birds in Nepal, and one of the most important in Asia. It is surrounded by a buffer zone of 173 km2, in which over 80,000 people live, most of whom are dependent on the natural resource base for their livelihoods. Uncontrolled fish harvesting has severely depleted fishery resources depriving local fishermen of their major source of subsistence. Annual waterfowl count has indicated a rapid decline of bird species that are heavily dependent on fish populations. The Darwin Initiative project is assisting local communities around KTWR in managing buffer zone wetlands for sustainable livelihoods, whilst enhancing wetland biodiversity, thus reducing the pressure on resources within KTWR Key words: Ramsar site, globally threatened species, wetland, community, livelihood doi: 10.3126/banko.v19i3.2210 Banko Janakari, Special Issue February 2009, 36-39